REMEDIATING STUDENTS MISTAKES IN USING CALIDERS THROUGH DIRECT INSTRUCTION COMBINED WITH MACROMEDIA FLASH - F03106033, Andrinata Sastria; Sahala, Stevanus; TMS, Haratua (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: This research is held to remediate students mistake of Grade X in using caliders through Direct Instruction model combined with macromedia flash on Measuring material. The purpose of this research is to indicate the effectiveness of Direct Instruction model in remediating the students mistakes. This research is a Pre-Experimental Reserah Design of One Group Pre-Test post-Test Design. The subjects are 27 students of Grade X D SMA Negeri 1 Sungai Raya. The data is gathered by using observation sheet to record practices, pre-test and post-test, as well as validaton. All data is analyzed by using formula of mean score, percentage, and effect size. The result of this research indicates teh level the level of effectiveness of Direct Instruction model combined with macromedia flash is categorized as moderate in remediating students mistakes of Grade X by using caliders in measuring material with effect size = 0,74 for measuring outer diameter and 0,78 for measuring depth. Abstrak: Penelitian ini dilaksanakan untuk meremediasi kesalahan siswa kelas X dalam menggunakan jangka sorong dengan menggunakan model Direct Instruction berbantuan macromedai flash pada materi pengukuran. Tujuan dari penelitian ini adalah untuk mengetahui sejauhmana tingkat efektifitas model DI dalam meremediasi kesalahan siswa. Penelitian ini adalah sebuah penelitian Pre-Experimental Design dengan rancangan One Group Pre-Test Post Test. Subjek dari penelitian ini adalah siswa kelas X D SMA Negeri 1 Sungai Raya berjumlah 27 siswa. Data penelitian dikumpulkan melalui lembar observasi praktikum, tes kinerja praktikum pre-test dan post-test, serta evaluasi. Data tersebut dianalisa dengan rumus nilai rata-rata, presentase, dan effect size. Hasil penelitian menunjukkan tingkat efektifitas model Di berbantua macromedai flash tergolong sedang dalam meremdiasi kesalahan siswa kelas X menggunakan jangka sorong pada materi pengukuran dengan effect size= 0,74 pada pengukuran diameter luar dan 0,78 pada pengukuran kedalaman. Kata Kunci: Remediasi, Kesalahan, Jangka Sorong